Testing causal relation between energy consumption carbon dioxide emission and economic growth in Indonesia - Fauziah, binti Usop (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study attempts to identify the causal relationship among energy consumption, carbon dioxide emission and economic growth in Indonesia during the periods of 1970 to 2013. This paper use economic growth as dependent variable and energy consumption, carbon dioxide emission as independent variable. The Augmented Dickey-Fuller (ADF) and Philips Perron (PP) unit root test, Johansen and Juselius cointegration test, Normalized Equation, Vector Error Correction Model (VECM) and Granger Causality test are conducted in this study. By using Johansen and Juselius co integration test, the result indicated long run relationship between variables. Besides, there is no causality relationship from economic growth to energy , consumption. However, there is bidirectional causality from carbon dioxide emission to energy consumption in Indonesia.